Pathological complete response of multiple liver metastases from colon cancer successfully treated with conversion surgery: A case report. (March 2023) - Kitasaki, Nao; Abe, Tomoyuki; Inoue, Masashi; Kohata, Akihiro; Toyota, Kazuhiro
Abstract: Introduction and importance: Recently, the successful long-term survival of patients with unresectable distant metastases from colorectal cancer, who underwent conversion surgery after systemic chemotherapy, have been documented. Herein, we present a patient afflicted with ascending colon cancer and multiple unresectable liver metastases, who underwent conversion surgery, resulting in the complete disappearance of the pathological liver metastases. Presentation of case: A 70-year-old woman visited our hospital with a chief complaint of weight loss. A diagnosis of ascending colon cancer (cT4aN2aM1a [H3]: TNM classification 8th edition) stage IVa with RAS/BRAF wild-type mutation was made (four liver metastases up to 60 mm in diameter were observed in both lobes). After 2 years and 3 months of systemic chemotherapy (capecitabine, oxaliplatin, and bevacizumab), the tumor marker levels had decreased to normal ranges and all liver metastases showed partial responses with remarkable shrinkage. After confirmation of a liver function and a preserved future liver remnant volume, the patient finally underwent hepatectomy, involving partial resection of S4 and subsegmentectomy of S8, along with a right hemicolectomy. Histopathologic examination revealed that all liver metastases had completely disappeared, while regional lymph node metastases had changed into scar tissue. However, the primary tumor failed to respond to chemotherapy, resulting in ypT3N0M0 ypStage IIA. The patient was discharged from the hospital on the 8th postoperative day without any postoperative complications. She is currently on the 6th month of follow-up without any recurring metastasis. Clinical discussion: Curative surgery is recommended for resectable liver metastases of colorectal cancer (CRLM), be it synchronous or heterochronous. Up until now, the efficacy of perioperative chemotherapy for CRLM is limited. Chemotherapy has a double-edged aspect, where some cases have shown successful improvement in the treatment stage. Conclusion: To obtain the maximum benefit from conversion surgery, it is critical to incorporate the appropriate surgical technique, at the correct stage, in order avoid the progression to chemotherapy-associated steatohepatitis (CASH) in the patient. Highlights: Recently, the successful long-term survival of patients with unresectable distant metastases from colorectal cancer, who underwent conversion surgery after systemic chemotherapy, have been documented. To obtain the maximum benefit from conversion surgery, it is critical to incorporate the appropriate surgical technique, at the correct stage, in order avoid the progression to chemotherapy-associated steatohepatitis (CASH) in the patient.